Morning Talk Program: Innovation in Instilling Qur'anic Character in Elementary School Students in the Era of Globalization - Nyimas Fakhriah; Ermis Suryana (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
This study aims to examine the Morning Talk program as a learning innovation in instilling Qur’anic character in elementary school students in the era of globalization. This research employs a qualitative descriptive approach conducted at SD IT Insan Mandiri Cendikia Palembang, involving six Islamic Education and tahsin teachers as subjects. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that teachers have a comprehensive understanding of Qur’anic character, which encompasses not only the ability to read and memorize the Qur’an but also the application of its values in daily life. The implementation of the Morning Talk program is carried out routinely every morning through activities such as congregational Dhuha prayer, Qur’an recitation review, memorization, reflection on verses, and the delivery of advice and motivation. The program effectively instills values such as faith, discipline, honesty, responsibility, and social awareness. However, challenges include the influence of social media and the lack of parental support. The program has a positive impact on students’ behavior, making them more disciplined, polite, and enthusiastic in engaging with the Qur’an. Therefore, Morning Talk serves as a strategic learning innovation in developing students’ Qur’anic character, with the need for synergy between schools, families, and the community to ensure its sustainability.